Epidemiologic study of type 2 diabetes mellitus and metabolic syndrome in rural population of kurdistan province, Iran, in 2011–2017. Issue 3 (May 2019) - Ghafuri, Shahnaz; Ghaderi, Ebrahim; Fahami, Yaser; Rajabnia, Mohsen; Naleini, Seyyed Nima
Abstract: Background: Metabolic syndrome is a serious health problem and is associated with an increased risk of type 2 diabetes and cardiovascular disease. The aim of this study was to determine the status of these two diseases in the rural population of Kurdistan province, west of Iran. Methods: In this cross sectional study, 10, 496 villagers of Kurdistan province during the period from March 2011 to February 2017 were selected through randomized systematic sampling. Required information was collected using pre-made check list and the examinations were performed. The data were analyzed with SPSS v22 software using chi-square test. Results: In the present study, the mean age of the population was 46.0 ± 14.13 y/o and 49.2% people were male and 50.8% were female. The prevalence of metabolic syndrome was 22.1% and for type 2 diabetes the prevalence was 19.6%. Hypertension was significantly higher in women (p < 0.001). There was a significant difference between the two sexes in terms of waist circumference, type 2 diabetes and metabolic syndrome. There was a significant difference between age groups with hypertension, waist circumference, type 2 diabetes and metabolic syndrome (p < 0.001) and a significant relationship between educational status with hypertention, waist circumference, type 2 diabetes and metabolic syndrome (p < 0.001). The results also showed that the relationships between age group and gender with BMI was significant (P < 0.001). Conclusion: The prevalence of diabetes in the rural population of Kordestan province is moderate but it has a high prevalence in metabolic syndrome. Educational and healthcare interventions seem to be necessary to reduce these prevalences, especially among women and in older ages. Highlights: The prevalence of metabolic syndrome and diabetes in the female population was higher than that of men. With the age elevation, the values of high blood pressure, waist circumference and type 2 diabetes increased. Higher educational level was associated with better status of type 2 diabetes and metabolic syndrome. The frequency of diabetes was highest in Sanandaj and Dehgolan and was lowest in Qorveh and Divandarreh. The highest prevalence of metabolic syndrome was reported in Marivan and Sarvabad and the lowest in Qorveh and Kamyaran.